Safety issues in vasculitis: infections and immunizations in the immunosuppressed host - Isada, Carlos M (Cleveland Clinic journal of medicine, 2012)
Infectious diseases are a significant cause of morbidity and mortality in immunosuppressed patients, including those with connective tissue diseases. Both disease and treatment contribute to a predisposition to infection in immunocompromised patients. Significant infection and morbidity occur in 25% to 50% of these patients with a median mortality of 5.2% due to common bacterial infections, such as pneumonia or bacteremia, and opportunistic fungal infections such as Pneumocystis. The lungs, skin, urinary tract, blood, and central nervous system are commonly affected. Pathogens such as Pneumocystis jirovecii, Histoplasma capsulatum, Aspergillus species, herpes zoster, JC virus, Nocardia asteroides, and Nocardia species are increasingly prevalent in immunocompromised patients. Improved recognition, diagnosis, and prevention of these infections are needed to enhance outcomes in these patients.